Dapsone‐induced methemoglobinemia in renal transplant recipients: more prevalent than previously thought. Issue 1 (12th November 2013) - Mitsides, N.; Green, D.; Middleton, R.; New, D.; Lamerton, E.; Allen, J.; Redshaw, J.; Chadwick, P.R.; Subudhi, C.P.K.; Wood, G.
Abstract Background After an outbreak of Pneumocystis pneumonia (PCP) in our nephrology unit, dapsone was used as the second‐line chemoprophylactic agent. Dapsone is the most common cause of drug‐induced methemoglobinemia (MHb). Its prevalence is poorly described in the renal transplant population. Because dapsone is excreted by the kidneys, we hypothesized that the rate of MHb in these patients would be higher than previously reported. We aimed to describe the demographics, risk factors, and presenting features of MHb in these renal transplant patients. Methods Twenty‐six transplant recipients commenced on dapsone for chemoprophylaxis against PCP from February to September 2011. All patients had normal glucose‐6‐phosphate dehydrogenase levels before treatment. Characteristics of patients with MHb were compared with those of the rest of the cohort to determine potential risk factors. Results Twelve (46%) patients developed MHb (levels 6.4 ± 4.1%). Six (50%) of the patients with MHb were asymptomatic on presentation. Cases had a mean drop in hemoglobin of 19 ± 7%. MHb led to five admissions (median length of stay 5 days, range 1–10 days). MHb level showed a strong correlation with the length of stay (correlation coefficient 0.762, P = 0.002). Conclusion This is the highest reported prevalence of MHb, to our knowledge, in patients receiving dapsone, and its use led to significant hospitalization in this population. This study raises concerns about the use of dapsone as chemoprophylaxis in renal transplant recipients.